Language as a factor in the cultural identity formation - Шостак, Оксана Григорівна (Київський інститут Національної гвардії України, 2025)
Еach identity has a mandatory connection with a certain culture, the values of which are revealed in the process of socialization and acculturation. The culture of each individual community serves as a source of sociocultural identity of this community. The formation of individual and collective identities of members of the indigenous community occurs on the basis of autochthonous cultural and semantic codes.
Keywords: Тези; Identity; Cultural identity; National identity